The Strategy of Determining Job Descriptions on Employee Performance PT. Fokus Kualitas Utama - Laylla Ma’rifatul Khasanah; Nuruni Ika Kusuma Wardani (STIKes Ibnu Sina Ajibarang, 2024)
This research was conducted to examine how the role of the job description on the performance of employees of a company. The method used by the researcher in this research is literature or literature study, so that the data obtained comes from previous research related to the same topic, namely the role or influence of job descriptions on employee performance. With this library research method, re-searchers must first collect previous research that can support data collection in this research. The results of this study indicate that the job description has a large and significant role in the quality of employee performance. Companies that al-ready have good, correct, and clear job descriptions will also have high quality work because employees will easily understand what duties, authorities and re-sponsibilities must be carried out in accordance with their position or position